Epidemiological, clinical and therapeutic aspects of cerebral malaria imported in Albania - Ndreu, Arben; Hajdari, Diana; Ndoni, Anduena; Shkurti, Klodiana; Kraja, Dhimiter; Como, Najada; Bino, Silva; Gjermeni, Nevila; Domi, Rudin; Mingomataj, Ervin C (The Journal of Infection in Developing Countries, 2016)
This is a case-report of two patients with cerebral malaria (CM) imported from West-African countries. Notably, this form of malaria was developed as a second disease episode, while the first episode was experienced in West Africa. These findings suggest that the second episode of malaria was caused by a different strain of Plasmodium falciparum as compared to the first one. They are the first cerebral malaria cases imported in Albania after the eradication and absence of Plasmodium for five decades. Early treatment of cerebral malaria is decisive on the duration of coma and disease’s outcome.